The Participation In Ecotourism Development Mangrove - Kuwat Riyanto (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2021)
Tarumajaya Bekasi has pristine mangrove areas, which is located on the west of Bekasi. It has a lot of potential that can be developed. One of the potential developed is Mangrove Ecotourism Jembatan Cinta Mangrove, where the management is done directly by the People Tarumajaya Bekasi. But a lot of potential that there is not explored properly and the tendency is decreasing environmental quality. Mangrove Ecotourism have not optimized yet its potential tourism destination object. Planning done by the Tarumajaya Bekasi Community performed not optimal. Therefore, in this study needs to be conducted to identify the level of community participation in the development of ecotourism in the Jembatan Cinta mangrove in order to develop good ecotourism planning through participation planning